Thoughts on Pólya’s legacy - Schoenfeld, Alan (Teaching Mathematics and Computer Science, 2022)
There is a saying, "the older I get, the smarter my parents become." What it means, of course, is that the more we learn, the more we appreciate the wisdom of our forebears. For me, that is certainly the case with regard to George Pólya. There is no need to elaborate on Pólya’s contributions to mathematics – he was one of the greats. See, for example, Gerald Alexanderson’s (2000) edited volume The Random Walks of George Pólya, or Pólya’s extended obituary (really, a 53-page homage) in the November 1987 Bulletin of the London Mathematical Society (Chung et al., 1987). Pólya was one of the most important classical analysts of the 20th century, with his influence extending into number theory, geometry, probability and combinatorics.